Purifikasi Jabatan Menteri Dari Partai Politik: Tinjauan Filsafat Ketatanegaraan Islam Al-Ghazali - Utomo, Hery Dwi (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2024)
The phenomenon of concurrent positions when the position as Minister and also occupies the position of a member of a political party shows that there is often a conflict of interest if the Minister's position is affiliated with a political party. This study looks at the relevance of these problems with Al-Ghazali's thinking which in its concept juxtaposes government with the principles of theology, this research is conducted with normative legal research with a philosophical approach. This research shows that the review of Al-Ghazali's constitutional philosophy can be seen as an effort to ensure that a minister can devote his full attention to the moral and ethical responsibilities associated with his government, without being hindered by party political interests. Al-Ghazali regarded the office of minister as a mandate that must be carried out with sincere intentions and responsibility for the welfare of the people. Moral and spiritual principles should be the foundation of policies should be driven by values that can benefit everyone. Ministers who are free from political affiliations will be better able to do their jobs in a way that is fair, objective, and responsible to both the people and God.